Non-discrimination in tax treaties : selected issues from a global perspective - Pistone, Pasquale; Weber, D. M. (Dennis Manolito), 1970- (EC and international tax law series, 2016)
The principle of non-discrimination is an evergreen of international tax law. While the principle's core concept remains stable, its importance in tax matters keeps growing. As its implications, regional dimensions and topical applications very frequently change around the world, constant monitoring and updating is essential to seize its current essence. This book aims to find a global dimension of the non-discrimination principle in tax law through the analysis of issues with theoretical and practical importance. It contains contributions from nine leading European and international tax law experts.--